Resealed Erythrocytes as a Carrier for Drug Targeting: A Review - Kumar, Manish (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Erythrocytes are the most abundant cells in the human body ( 5.4 million cells/mm3 blood in a healthy male and 4.8 million cells/mm3 blood in a healthy female) having potential carrier capabilities for the delivery of drugs and drug loaded microspheres. Drug-loaded carrier erythrocytes (resealed erythrocytes) are prepared simply by collecting blood samples from the organism of interest, separating erythrocytes from plasma, entrapping drug in the erythrocytes, and resealing the resultant cellular carriers. encouraging the use of erythrocytes in drug delivery include various advantages like as remarkable degree of biocompatibility, Complete biodegradability, lack of toxic product, controllable life-span, decreasing drug side effects etc. In this review we discuss about Resealing of erythrocytes, various techniques of drug loading such as hypotonic hemolysis, hypotonic dilution, hypotonic pre-swelling, isotonic osmoticlysis, Chemical perturbation of the membrane, Electro-insertion, Entrapment by endocytosis etc. and it?óÔé¼Ôäós applications in various fields of human and veterinary medicine. Key Words: Resealed erythrocytes, Carrier, Drug loading, Electro-insertion.